Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content1. Managing the Archaeological Records: Present Practices and Future TrendsCo-Prof. Mohammed Ali Al-Belushi2. The role of the mobile museum in promoting National Identity and the Background Kingdom of Saudi ArabiaCo-Prof. Noha Saeed Nagaiti, Mrs. Mrouj Hatem Qurban3. The Representation of the Social and Political Reality in the Palestinian Cinema: Mashrawi's film "Laila's Birthday"Dr. Ghada Hamdi Alraee4. Research data management and its role in developing scientific researchMrs. Tahani Mohammed Mousa5. The role of the Herzliya Institute in Israeli decision-makingDr. Elham Jabr Salm Shamali, Mrs. Nedaa Mohamad Kishko6. The Level of Effectiveness of Social Upbringing Methods in Promoting Public Taste of Saudi Society  (An Applied Study on a Sample of Male and Female Teachers in the City of Dammam in the Eastern Region of Saudi Arabia)Mrs. Albanderi Saad Alqahtani, Dr. Olfa Ahmed Mejri7. The role of the United Nations in protecting the rights of refugee children (An analytical study)Mrs. Sarah Mohammed Al-Qahtani, Dr. Rawa Ghazi Al-Makki8. Sociological analysis to the communicative technological systemMaitreconference\ Zenkoufi Fouzia Bent Mahmoud , Dr. Korzet Najima Bent Abd Elkader
Keywords: Journal of Humanities & Social Sciences